PENGARUH MOTIVASI KERJA, KEMAMPUAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PADA THE ST. REGIS BALI RESORT - Kadek Dennisa Anjelia Pramusti; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (VALUES, 2024)
Employee performance is the result of work, both quality and quantity, produced by the employee or the real behavior displayed in accordance with the responsibilities given to him. The factors that influence employee performance in this research are work motivation, work ability and leadership style. This research aims to determine the influence of work motivation, work ability and leadership style on performance at The St. Regis Bali Resort. The population in this study were all employees at The St. Regis Bali Resort, numbering 341 people. Determining the number of samples using a purposive sampling technique with a sample size of 77 employees. The data analysis technique used is multiple linear regression analysis. The test results show that work motivation, work ability and leadership style have a positive and significant effect on employees at The St. Regis Bali Resort.